The Situational Leadership Style In Education - Agus Fahmi (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2019)
Situational leadership plays an important role in improving the performance of teachers because of situational leadership is the ability of a leader to direct subordinates in carrying out tasks according to their readiness but in fact the principal still participate less in giving examples of how to work right on subordinates. The focus of the problem is knowing how to apply situational leadership in education. Become subjects in this study is a teacher with a population of 46 people. Data collection techniques used questionnaire as the principal method while the method of observation and documentation as a complementary method. Further data analysis is the method of statistical analysis with Simple Linear Regression formula. Based on the analysis of data obtained value of 7.438 t_count further the value of consultation with t_table value of 1.679 at significance level of 5% with N = 46 The facts demonstrate that t_hitunglebih value greater than the value tcount > ttable or 7.438 > 1.679. Keywords: Situational Leadership in Educatio